The effect of lobbies' narratives on academics' perceptions of scientific publishing: An information provision experiment - Giulia Rossello; Arianna Martinelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This paper presents experimental evidence on the impact of opposite copyright lobbies' narratives on scholars' views toward the publishing system. We conduct the empirical analysis by running a large-scale information provision experiment on a representative population of European scholars. Scholars were individually randomized into a control group or one of two promotional videos presenting opposite lobbying interests. The first video presents the publisher's narrative, featuring publishers as innovative firms and the guardians of ethics and scientific advance. While the second presents copyright activists' narrative featuring publishers as greedy and unethical. We document scholars' general discontent towards the publishing system. However, both lobbyist narratives change perceptions towards their cause. Overall, publishers' lobbyist information has a slightly smaller persuasive effect, linked to a small part of the population that exhibits a strong emotional reaction. Additional information is accompanied by a slight increase in the probability of taking the action of being informed, especially when we control for the scholar's quality.
Keywords: D83; I23; O34; 330; Scientific Publishers; Academics' Perception; Information Provision Experiment; Copyright and Knowledge Diffusion